Optimization of Medium Fermentation for Production of Antimicrobial Compounds by Endofit Bacteria Andalas Plant (Morus macroura Miq.) B.J.T.A-6 Isolate - Nada Nafion; Dwi Hilda Putri; Irdawati Irdawati (Bioscience, 2019)
Cases of bacterial resistance to antibiotics are discussed with serious problems in the world of health. New antimicrobial compounds are needed which are more effective in treating infectious diseases. Isolate B.J.T.A-6 is an endophytic bacteria from Andalas plants (Morus macroura Miq.) which is known to be able to produce antimicrobial active compounds. Antimicrobial compounds can be produced by growing them on fermented media. The purpose of this study was to optimize the medium fermentation of Andalas endophytic bacteria of B.J.T.A-6  isolates in producing antimicrobial compounds. While medium fermentation is Nutrient Broth (NB), Muller Hinton (MH), and Luria Bertani Broth (LB). Antimicrobial activity tests were carried out by means of diffusion. The parameters used were the diameter of the inhibition zone against Staphylococcus aureus around the disc paper. The profile of medium fermentation optimization was analyzed statistically. The results showed that B.J.T.A-6  isolates could inhibit the highest growth of S. aureus by using LB fermentation medium.